PERAN SAINS UNTUK MENUMBUHKAN KARAKTER PESERTA DIDIKDALAM BINGKAI MASYARAKAT MULTIKULTURAL - Budiastra, A.A. Ketut; ., Hartinawati; ., Sardjijo (MAJALAH ILMIAH PEMBELAJARAN, 2012)
Human character mostly affected both by genetic inheritance as well as by theirexperience. The ways in which students develop are shaped by social experienceand circumstances within the contex of their life. The scientific question is justhow students experience and social experience interact in producing humancharacter. In general, science is universal which mean that what is occurred in oneplace also will be occurred in another place. Some values emerged from sciencesuch as honesty, truthfulness, respect other opinion and so on, as a result ofinteraction during science class in classroom setting. In this paper, also will bementioned the role of science in developing character of students especially forelementary school students. Moreover, at the end of this paper also be explainedtransaction position in curriculum development and their role in developingelementary school students character in multicultural societies.